On the application of the work-of-indentation appproach to depth-sensing indentation experiments in coated systems - Tuck, J; Korsunsky, A; Bull, S; Davidson, R (Elsevier, 2001)
The work-of-indentation approach is developed and applied for hardness calculations on soft or hard materials, and also for a range of coated systems. The method appears to be less sensitive than other definitions to the effects of pile-up observed in soft materials. Work-of-indentation hardness is calculated directly from the energy of indentation without the need for estimating penetration depths, areas or volumes, which can be time consuming and inaccurate. In particular, using the plastic component of the work-of-indentation yields consistent results across the range of materials studied. The method breaks down, however, at very low loads and small penetration depths, which is likely to be due to deviations from the ideal tip geometry.